Enhancing Urban Resilience to Extreme Heat in Zambia: Strategies and Interventions in Infrastructure Planning - Happy Mpezeni; Shi, Yijun (International Journal of Social Sciences and Public Administration, 2025)
The rising frequency of extreme heat events, particularly in urban areas has emerged as a significant concern with climate change anticipated to exacerbate this phenomenon across various regions worldwide. This paper explores the critical dimensions of enhancing urban resilience to extreme heat in Zambian, elucidating strategies tailored to the country's socio-economic, geographical, and climatic characteristics. The analysis underscores the pivotal role of prioritizing green infrastructure, sustainable urban design, and community-centric approaches in mitigating the impacts of extreme heat. By emphasizing the interconnected nature of these strategies and their relevance to Zambia's diverse urban settings, the review offers tailored insights for policymakers and urban planners. Additionally, it stresses the importance of robust early warning systems and capacity-building initiatives, aligning them with the unique challenges faced by Zambian communities. This endeavour, crucial for policy-makers and researcher, contributes essential knowledge for fostering sustainable, resilient, and adaptive urban environments in Zambia and other regions faced with similar issues.